Effect of Diabetes Mellitus on Successful Treatment of Tuberculosis in Tanah Kalikedinding PHC - Zeni Yanti (Universitas Airlangga, 2017)
Tuberculosis is an infection disease caused by Mycobacterium tuberculosis. According to WHO in 2014 among 9,6 billion people in the word infected TB. In Indonesia there are 647 cases at 100.000 population. Est Jawa had the both contributor of TB cases after West Java. Surabaya is the district with the highest level TB case in East Java. National indicator of successful treatment is Success Rate. SR throughout Surabaya district in 2015 is 79.21%, (national standard ≥85%). Tanah Kalikedinding primary health care had SR decreased 82.1%, 81.2% and 68.33%. Failure TB Treatment caused low these SR. One of the caused of this, is high level of diabetes mellitus incident. The purpose of this research to find the influence of diabetes mellitus to successful of TB Treatment. The study design is cross sectional, the sample used were 55 pulmonary tuberculosis patients at Tanah Kalikedinding Primary Health Care. Statistic test used logistic regression with α= 0.05.The result of logistic regression p = 0.012 means that there is influence between diabetes mellitus with the successful treatment of Pulmonary Tuberculosis. OR value = 2.056 means that patient pulmonary tuberculosis without diabetes mellitus has the possibility recover 2.056 times greater than the patient pulmonary tuberculosis with diabetes mellitus. Diabetes mellitus screening in the Tuberculosis early treatment, appropriate treatment and monitoring is a step that can be done by Tanah Kalikedinding PHC Surabaya to minimize the incidence of failure treatment of Tuberculosis with diabetes mellitus. Keywords: Diabetes Mellitus, Successful Treatment, Success Rate, Tuberculosis